DANDUPALYA: THE REALITY CHECK ON MODERN CRIME - Chakrabarty, Andrew Reginald (European Scientific Journal, ESJ, 2014)
Crime has now taken on a new avatar. It is new, evolved and now, without reason. At the very inception of this pursuit to go into the depths of modern crimes, it must be said that the study of the notorious gang of ‘Dandupalya’ (India) does not only open the back doors and throw light on the effect of Indian criminal laws alone but also springboards to a much more universal subject which deals with the effectiveness of deterrent values of criminal laws and highlights certain social problems that Indian society is inherent with. Certain parallels have also been drawn with established theories of criminology to try and understand the mindset of the gang itself thus highlighting aspects of education, environment etc. with relation to crime causation in India. The reasons of crime causation have now come to light in a new and unprecedented way all due to the actions of this notorious gang. ‘Dandupalya’ is a small village situated near Bangalore (India) and was bought into the limelight when a dozen members of an extended family, some of who settled in the village began killing and looting at will. They were known as ‘The Dandupalya Gang.’ This was the first instance of such crime in India where there was barely any motive, no provocation, absolute disregard for consequences and ruthless and large scale murder, rape and theft at will. Shockingly, they had a persistent obsession with slitting throats as well which was the signature trait of the gang itself. A parallel has further been drawn between a restricted scope of organized crime, and the ‘Dandupalya’ crime spree while studying the failure of police functions in this regard and thus exposing the mindset of these criminals with regards to their deviant functioning.